Evaluación de la pesquería de Lutjanus peru (Pisces: Lutjanidae) de . Guerrero, México - Santamaría, Apolinar (1999)
Red snapper (Lutjanus peru) fishery was analyzed from landings and catch records. Stock age structure was reconstructed after the parameter values of the von Bertalanffy growth model, the length-weight relationship, ages and the natural mortality coefficient through each of nine years of cateh records. The Pisat software package was applied to assess population parameters, whose estimates are, for the von Bertalanffy growth model, K = 0. 1 442 to 0.38; lo = -0.2; L = 87 cm; W = 9.4 Kg, and the natural mortality coefficient (M) afier several methods (0. 14 to 0.38). Cohort size was assessed by the virtual population analysis (VPA), estlmating population size in 5.2* 1 06 fish with a biomass of 8 454 tonnes. Current fishing mortality P, ranges from 0.06 to 1 . 1 3, depending upon the chosen M value; according to this, when the M value used is low, the results suggest that the stock is nnderexploited, and vice versa. The yield per recruit model applied suggests improvements to the management strategy. The model indicates recruit overfishing because very small fish are the main target (te